Хеппи-энд для Дездемоны - Донцова Дарья Аркадьевна (Иронический детектив, 2007)
Экземпляры: ф.22 (2007) / Инвентарный номер: 51465 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 67 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44